Examining Some of The Students’ Challenges in Learning Organic Chemistry - Issa I. Salame; Sagar Patel; Shafic Suleman (Universitas Islam Indonesia, 2019)
Organic chemistry is often regarded as a difficult subject which deters learners and is associated with poor performance. Our research aims to examine some of the challenges that students face in learning organic chemistry topics related to acid/base and resonance structures theories. For this purpose, organic chemistry exams were analyzed in regards to these troublesome topics. A questionnaire was administered to further understand some of the challenges students face when enrolled in organic chemistry. Our data show that students face several challenges learning these topics and that there is a need to change the way these topics are addressed in instruction.